2013
DOI: 10.12691/ajcmr-1-2-3
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Fetal Outcome of Elective Caesarean Section at 37 – 38 Weeks versus 39 Completed Weeks of Gestation in Enugu, Southeast Nigeria

Abstract: A retrospective study comparing maternal and neonatal outcome of singleton fetuses delivered at 37-38 weeks of completed gestation with those delivered at 39 completed weeks of gestation or longer by elective caesarean section at the University of Nigeria Teaching Hospital, Enugu between January 1, 2004 and December 31, 2008. There were 164(21.3%) elective caesarean deliveries during the study period. 117 (71.3%) were performed between 37-38 weeks of completed gestation and 47(28.7%) at 39 completed weeks of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
(17 reference statements)
1
2
0
Order By: Relevance
“…Current study demonstrated that BMI was directly associated with FTOL, this relationship was shown by several previous studies like; [13] [19] demonstrated that the risk for caesarean delivery increases as BMI increases > 40 among nulliparous extremely obese women attempting a trial of labor, further increases in BMI > 40 among parous women attempting a TOL does not seem to add additional risk for cesarean delivery [24]. [25] study (reviewed 1.516 patients who underwent VBAC and found that an inter delivery interval of less than 19 months was associated with a decrease rate of successful VBAC). In contrast, Bujold and colleagues, reviewed 1.527 women attempting VBAC and found that an inter delivery interval of 24 months or less was associated with no difference in VBAC success rates [21].…”
Section: Discussionsupporting
confidence: 63%
“…Current study demonstrated that BMI was directly associated with FTOL, this relationship was shown by several previous studies like; [13] [19] demonstrated that the risk for caesarean delivery increases as BMI increases > 40 among nulliparous extremely obese women attempting a trial of labor, further increases in BMI > 40 among parous women attempting a TOL does not seem to add additional risk for cesarean delivery [24]. [25] study (reviewed 1.516 patients who underwent VBAC and found that an inter delivery interval of less than 19 months was associated with a decrease rate of successful VBAC). In contrast, Bujold and colleagues, reviewed 1.527 women attempting VBAC and found that an inter delivery interval of 24 months or less was associated with no difference in VBAC success rates [21].…”
Section: Discussionsupporting
confidence: 63%
“…The incidence of caesarean deliveries at the University of Nigeria Teaching Hospital is 25% with elective caesarean section constituting 21.3% of all caesarean deliveries (Okezie, Oyefara & Chigbu, 2007;Okeke et al, 2013). There is a growing opinion that elective caesarean section should not be done before 38 weeks unless there is evidence of foetal lung maturity to avoid adverse neonatal outcomes (Treffers, 1993: Okeke et al, 2013.…”
Section: Incidence Of Csmentioning
confidence: 99%
“…The incidence of caesarean deliveries at the University of Nigeria Teaching Hospital is 25% with elective caesarean section constituting 21.3% of all caesarean deliveries (Okezie, Oyefara & Chigbu, 2007;Okeke et al, 2013). There is a growing opinion that elective caesarean section should not be done before 38 weeks unless there is evidence of foetal lung maturity to avoid adverse neonatal outcomes (Treffers, 1993: Okeke et al, 2013. Several studies have documented high incidence of respiratory problem, the newborn special care unit admission, prolonged hospitalisation, low Apgar score, iatrogenic prematurity, surfactant deficiency, and transient tachypnoea of newborn (Donaldson & Dagbjatson, 2007), following elective caesarean delivery (Okeke et al, 2013).…”
Section: Incidence Of Csmentioning
confidence: 99%